The online marketplace advantage : sell more, scale faster, and create a world-class digital customer experience - Corrot, Philippe; Nussenbaum, Adrien (Ascent Audio, 2023)
Revolutionize your business with the power of marketplaces In today's digital-first economy, marketplaces are growing at twice the rate of overall eCommerce-and proving that traditional eCommerce is no longer enough. With The Online Marketplace Advantage: Sell More, Scale Faster, and Create a World-Class Digital Customer Experience, the duo behind more than 300 of the world's most successful marketplaces reveals the strategies every enterprise needs to take the lead. Through dozens of case studies, real-word examples, and proprietary marketplace research you'll learn: - How to turn the marketplace model into your business's competitive advantage - The make-or-break decisions for launching an industry-leading enterprise marketplace fast - The best practices to achieve marketplace scale, and the most common pitfalls that separate the winners from the losers With The Online Marketplace Advantage, discover the complete playbook you need to break through with a successful, scalable marketplace strategy that puts your business on a path to unprecedented growth-permanently.